Studies on Removal of Selected Pharmaceutical Contaminants using TiO2-bionanocomposite - Chauhan, Anjali (My University, 2024)
The widespread contamination from pharmaceutical industries through wastewater effluents and improper disposal of unused medicines is a significant environmental and public health concern. Many economically developing nations, including India, face constant health risks due to the presence of pharmaceutical active compounds (PhACs) with uncontrolled discharge limits. These PhACs, which include pharmaceuticals and personal care products, are non-biodegradable organic compounds that cannot be effectively removed through conventional treatment techniques. The prevalence of antibiotics in aquifers, in particular, may lead to the emergence of antibiotic-resistant microorganisms. Moreover, the uncontrolled discharge of pharmaceutical contaminants into major water streams, and their potential entry into the food chain, poses serious human and eco-toxicological risks. The present work, thus is an attempt to develop strategies for the efficient removal of selected pharmaceutical contaminants under environmentally relevant conditions using TiO₂-based bio nanocomposites. The Fe doped TiO2 nanoparticles were synthesized using chemical precipitation method. Material characterizations confirmed the effective substitution of Ti4+ ions by Fe3+ ions, resulting in the band gap narrowing of pure TiO2 and facilitating the excitation of the Fe-doped TiO2 photocatalyst under natural sunlight. Theoretical modeling based on density functional theory (DFT), revealed that the Fe ions within the TiO2 lattice are effectively confined, further narrowing the wide band gap. Optimization studies identified a doping ratio of Fe:Ti = 1.5 as the most effective for the photocatalytic degradation of the norfloxacin (NFX) drug. However, the photocatalytic efficacy of nanomaterials has traditionally been limited by sensitivity to operational parameters and the lack of a predictive mathematical model. Therefore, the photocatalytic potential of Fe-doped TiO2 was comprehensively evaluated using a three-level Box-Behnken design (BBD). Response surface methodology analyses indicated that a water sample containing 10 ppm NFX could be degraded by up to 98.3% within three hours using 0.8 mg/mL Fe-doped TiO2 at a pH of 7.2 under sunlight. The roles of various reactive species (i.e., •O2-, •OH, and h+) were analysed, revealing that holes and hydroxyl radicals were the primary active species in Fe-TiO2-based photocatalysis. The presence of anions such as NO3-, Cl-, and HCO3– ions significantly hindered photodegradation potential. Additionally, the toxicity of degradation intermediates was assessed through bacterial and phytotoxicity tests, conforming the ix environmental safety of treated water. The in-vitro toxicity of the nanomaterial was also examined, emphasizing its environmental implications. Furthermore, the synthesized catalyst demonstrated ~99% of photocatalytic disinfection against Escherichia coli and Staphylococcus aureus with sustained recyclability, maintaining 82% degradation efficiency over five cycles. The aggregation of TiO₂ nanoparticles and their recovery from treated water are the two major challenges in translating this strategy into practical applications. Immobilizing TiO₂ onto a cellulose matrix derived from agro-waste addresses these issues by enhancing TiO₂ dispersion and providing a reusable, eco-friendly platform for photocatalysis. The extraction of cellulose from sugarcane bagasse for the development of bionanocomposites aligns with green chemistry principles and resource utilization too. The incorporation of Fe-doped TiO2 nanoparticles into regenerated cellulose-based film resulted in the desired morphological and physicochemical properties for effective photocatalysis. The photocatalytic performance of these films were tested against model drugs, ibuprofen (IBF) and carbamazepine (CBZ) under solar light irradiation. Under optimized conditions, the nanocomposite film exhibited 94.7% and 92.6% degradation of ibuprofen and carbamazepine, respectively. The effect of initial drug concentration, solution pH, and reactor A/V ratio were studied and modeled using Langmuir–Hinshelwood (LH) reaction kinetics. Up to five reuse, the nanocomposite demonstrated significant contaminants elimination (89% IBF, 87.3% CBZ) offering remarkable recyclability. Scavenging studies identified (•OH) and holes (h+) as the primary species responsible for photocatalytic activity. The degradation mechanism of IBF and CBZ was confirmed through HPLC-MS/MS analyses, showing complete degradation without leaving toxic intermediates. The water treated with nanocomposite film was safer to plants, and disinfection studies under solar light displayed >97% efficiency in eliminating E.coli and S. aureus, present in water samples. The nanocomposite films also exhibited biodegradability under natural condition. In conclusion, the findings of this study suggest that the synthesized Fe-doped TiO₂ hybrid films are sustainable, portable, and suitable for real-time applications. They offer a viable solution for removing pharmaceutical contaminants from water systems, with the potential to mitigate risks associated with antimicrobial resistance and environmental pollution. The TiO₂-based bionanocomposite films provide a promising approach to address the challenges posed by pharmaceutical pollutants while contributing to the development of sustainable, green technologies for wastewater treatment.
Ph.D. thesis
Keywords: Photocatalyst; DFT Simulation; Treated wastewater; Bionanocomposites